Salmon rest raw material flow—without a trace? Assessing resource efficiency of salmon processing in Germany - Barrelet, Johna; Brüning, Simone; Simons, Sarah (Frontiers in Sustainable Food Systems, 2025)
Maximizing resource efficiency and reducing waste in fish processing are key to enhancing economic productivity, conserving resources, and ensuring nutritional security. However, publicly accessible data on seafood processing residues in Germany remain unavailable, making it difficult to accurately assess resource efficiency. Considerable quantities of salmon are processed in the country, generating residues, co-products or by-products, herein summarized under rest raw material (RRM). To address this data gap, volumes, utilization, and applications of salmon RRM for 2020 were systematically collected, mapped, and analysed using material flow analysis (MFA). Results highlight the quantities available at each step along the value chain and the current utilizations of this biomass. The applied mixed-methods approach, incorporating industry reports, surveys, expert interviews, and official statistics, revealed that salmon processing generates around 19,500 tonnes of RRM in Germany. When factoring in imports, nearly 40,000 tonnes of RRM are processed in total. Of all salmon raw material processed in Germany, 98% is utilized for food and feed and only about 2% go into disposal. Less than 1% of produced food-grade salmon oil and meal is used for domestic human consumption. In light of these results, the potential for transforming salmon rest raw material into high-value products, making use of its valuable bioactive compounds, is discussed, considering current challenges, such as their confinement to niche markets or procedural difficulties in need of resolution. These findings provide actionable insights that underscore the potential for strategic RRM management to enhance the economic and ecological sustainability of aquatic biomass processing, supporting global food security efforts.